Jalur Perdagangan Satwaliar Jenis Dilindungi antara Pulau Seram dan Pulau Ambon - Pelu, Aisa; Badaruddin, Ernywati; Kaya, Manuel (Universitas Pattimura, 2024)
Seram Island, rich in biodiversity, is a source of wildlife often sold illegally. This study aims to identify protected wildlife trade routes between Seram Island and Ambon Island. This study was conducted using a direct survey method in three main ports on Seram Island and several ports and airports on Ambon Island. The results showed that several protected bird species, such as cockatoos, parrots, and bays, are sold illegally. The trade route is generally through small ports with minimal supervision. The main obstacle in handling this illegal trade is the lack of human resources and strict supervision at these ports. This study recommends increased surveillance, socialization of wildlife protection laws, and stricter law enforcement to address this problem.